Proceso para fomentar y apoyar la adopción de DevOps en PyMEs de software - Orozco, Carlos; Pardo, César; Zuñiga, Karen; Certuche, Samuel-Camilo (Revista Científica, 2022)
This article presents a process to encourage and support the adoption of DevOps in small and medium software companies. The process was designed through the identification of elements suggested and identified in the literature through systematic mapping. The identified elements were harmonized, compared and integrated, resulting in a clear, homogeneous process without terminological conflicts composed of three sub-processes, roles, activities, artifacts, tools and process flows in BPMN as support for configuration management, integration, continuous deployment and monitoring from a fundamental and complementary approach of suggested practices. The proposed process was evaluated through a focus group made up of DevOps experts, who considered that the process is pertinent, clear, complete and applicable in small and medium-sized software companies. In short, the process describes a total of 82 activities, 16 artifacts, 9 roles and recommends 13 technological tools to support the automation of each of the activities related to each thread, which will guide professionals, companies and stakeholders to reduce the ambiguity and subjectivity in the understanding and adoption of DevOps.